2012
DOI: 10.1051/0004-6361/201219954
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the scintillation noise above different observatories measured with MASS instruments

Abstract: Aims. Scintillation noise is a major limitation of ground-based photometric precision.Methods. An extensive dataset of stellar scintillation collected at 11 astronomical sites world-wide with MASS instruments was used to estimate the scintillation noise of large telescopes in the fast photometry and traditional long-exposure regime.Results. Statistical distributions of the corresponding parameters are given. The scintillation noise is mostly determined by turbulence and wind in the upper atmosphere and is comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 29 publications
6
28
0
Order By: Relevance
“…7, we compare measured scintillation statistics from several major observatories around the world (Kornilov et al 2012) including the values we have determined for La Palma in Fig. 6.…”
Section: Comparing Measured Scintillation Noise With Young's Approximmentioning
confidence: 99%
See 1 more Smart Citation
“…7, we compare measured scintillation statistics from several major observatories around the world (Kornilov et al 2012) including the values we have determined for La Palma in Fig. 6.…”
Section: Comparing Measured Scintillation Noise With Young's Approximmentioning
confidence: 99%
“…This equation is regularly used by many astronomers (for example Southworth et al 2009) to estimate the scintillation noise in their measurements. Recent work by Kornilov et al (2012) showed that this equation tends to underestimate the median scintillation noise by a mean factor of 1.5.…”
mentioning
confidence: 99%
“…It is important to note that the quantities being summed are not correlated in the earlier paper [6], but our quantities are correlated. Moreover, equations (12) and (11) have the form of the sum of the log-normally distributed quantities only when Taylor series decomposition has been applied in the following way:…”
Section: Forecastingmentioning
confidence: 99%
“…The partial derivatives of γ 2,3 are calculated with respect to the implicit function theorem and using equations (11) and (12). The mean and the covariance of the log-normally distributed quantities i are exactly given by expressions (15) and (16).…”
Section: Forecastingmentioning
confidence: 99%
See 1 more Smart Citation